Screening for cancer in patients with unprovoked venous thromboembolism: protocol for a systematic review and individual patient data meta-analysis. Issue 6 (10th June 2017) - van Es, Nick; Gal, Grégoire Le; Otten, Hans-Martin; Robin, Philippe; Piccioli, Andrea; Lécumberri, Ramon; Palomares, Luis Jara; Religa, Piotr; Rieu, Viriginie; Rondina, Matthew T.; Beckers, Mariëlle M; Prandoni, Paolo; et al.
Abstract : Introduction: Occult cancer is present in 4%–9% of patients with unprovoked venous thromboembolism (VTE). Screening for cancer may be considered in these patients, with the aim to diagnose cancers in an early, potentially curable stage. Information is needed about the risk of occult cancer, overall and in specific subgroups, additional risk factors and on the performance of different screening strategies. Methods and analysis: MEDLINE, Embase and CENTRAL databases were searched from November 2007 to January 2016 for prospective studies that had evaluated protocol-mandated screening for cancer in patients with unprovoked VTE and with at least 12 months' follow-up. Two reviewers independently assessed articles for eligibility. Ten eligible studies were identified and individual patient data were obtained from each of them. Study quality was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool . Generalised linear mixed-effects models was used to calculate estimates in a one-stage meta-analytic approach, overall and in a number of subgroups, including patients undergoing limited screening only, elderly patients, patients with previous VTE, smokers and patients using oestrogens. Ethics and dissemination: Ethical approval is not required for this systematic review and individual patient data meta-analysis. Findings have been submitted for publication in peer-reviewed journals and presentations at national and international conferences to provide clinicians and other decision-makers with valid and precise risk estimates of occult cancer, overall and in specific clinical subgroups, with risk factors for occult cancer, with estimates of the diagnostic performance of limited screening and with an exploration of the benefit of extensive screening strategies.